2018
DOI: 10.1038/s41598-018-27387-0
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann modeling to explain volcano acoustic source

Abstract: Acoustic pressure is largely used to monitor explosive activity at volcanoes and has become one of the most promising technique to monitor volcanoes also at large scale. However, no clear relation between the fluid dynamics of explosive eruptions and the associated acoustic signals has yet been defined. Linear acoustic has been applied to derive source parameters in the case of strong explosive eruptions which are well-known to be driven by large overpressure of the magmatic fluids. Asymmetric acoustic wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Differences between observed Sakurajima νN and modeling results may be due to to additional complications from finer‐scale meteorological structures (e.g., convective winds in canyons) and/or spectral contributions from complex source dynamics. Our modeling work has been limited to a simplistic Gaussian acoustic source function yielding nearly symmetrical waveforms that poorly match observations (Figure ), but recent work with fluid‐dynamical sources have modeled asymmetrical waveforms even with linear acoustic propagation (Brogi et al, ; Cerminara et al, ). Three‐dimensional wavefield effects are also likely significant, as our approach is limited to a 2‐D axisymmetric cylindrical geometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between observed Sakurajima νN and modeling results may be due to to additional complications from finer‐scale meteorological structures (e.g., convective winds in canyons) and/or spectral contributions from complex source dynamics. Our modeling work has been limited to a simplistic Gaussian acoustic source function yielding nearly symmetrical waveforms that poorly match observations (Figure ), but recent work with fluid‐dynamical sources have modeled asymmetrical waveforms even with linear acoustic propagation (Brogi et al, ; Cerminara et al, ). Three‐dimensional wavefield effects are also likely significant, as our approach is limited to a 2‐D axisymmetric cylindrical geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinear propagation has been proposed as a possible explanation for asymmetric infrasound waveforms, which are commonly observed at volcanoes worldwide (e.g., Anderson et al, ; Fee et al, ; Marchetti et al, ; Matoza et al, ; Medici et al, ). However, this phenomenon can alternatively be explained with linear propagation and crater rim diffraction (Kim & Lees, ) or fluid flow at the source (Brogi et al, ). For lack of quantitative understanding of near‐source acoustic nonlinearity, volcano‐acoustic studies commonly assume linear propagation (e.g., Garcés et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They focused on short duration explosions and their simulations show an acoustic wave propagating away from the vent in all directions, trailed by a jet of eruptive fluid extending upwards from the vent. Brogi et al (2018) showed that the radiation pattern became more anisotropic as the exit velocity was increased, with larger pressure amplitudes above the vent than to the side. Due to their use of a Lattice Boltzmann numerical method, however, their simulations were limited to subsonic velocities (  0.5 M where M is the Mach number).…”
Section: 1029/2021jb021940mentioning
confidence: 99%
“…These signals feature a rapid compression followed by a rarefaction phase with a nearly symmetrical shape (e.g., 5 d, g, and Supplementary Material SM2), which is indicative of a flow rate source time function symmetrically distributed in time around a peak value (Brogi et al, 2018;De Angelis et al, 2019). In other instances waveforms are non-symmetrical, exhibiting rapid compression onsets followed by rarefaction phases with reduced amplitudes (e.g., 5 a); waveform asymmetry may represent either a non-symmetrical flow rate source function, or reflect a shock-type source mechanism similar to blast waves produced by chemical explosions (Marchetti et al, 2013;Brogi et al, 2018). Typically, blast waves can be separated from other explosion mechanisms due to their characteristic appearance and much larger peak amplitudes, of the order of several hundreds of Pa at few hundred meters from the source.…”
Section: Infrasound Signals At Volcán De Fuegomentioning
confidence: 99%